Quality and inclusion in education : the persisting challenges - Varghese, N.V.; Mangalagiri, Anjana, 1953-; Mathew, A. (New York : Routledge, 2023)
"This book calls for an equitable and qualitative access to education for all. It proposes paradigms of educational governance that are based on coalition building between key stakeholders, are grounded in local and cultural contexts, sensitive to the language needs of communities. It underlines the significance of gender sensitive and inclusive approaches that ensure equity for marginalized children and minorities. Based on research-based studies, the volume focuses on equity, quality, and learning - covering a broad spectrum, from school to higher, to adult education. It discusses the multiple learner deprivations amongst the marginalized communities and the severe impact of events such as pandemics that exacerbate learner inequities and the recent developments in India under the National Education Policy 2020. It also presents research-based country experiences in the Asian (India, Bangladesh, China) and African (Ghana, South Africa) contexts, showing how external influences on the changing priorities in policy perspectives cut across developing countries. Compiled in honour of Professor R. Govinda, this volume of insightful articles will be of interest to students and researchers of educational policy and studies, sociology of education, equity and human rights. It will also be useful for decision makers and think tanks"--
Keywords: Educational equalization -- United States; Mainstreaming in education -- United States; Educational innovations -- United States; EDUCATION / Educational Policy & Reform / General; EDUCATION / Research